Peculiarities of Combined Mixing Caused by Instability of Mechanical Equilibrium of Isothermal Ternary Gas Mixture at Diffusion - Vladimir N. Kossov; Venera Mukamedenkyzy; Arsen Tolepbergen; Holm Altenbach (International Journal of Chemical Engineering)
In this work, the transition from diffusive to convective mixing in an isothermal ternary gas system (helium–argon–nitrogen) in which the density of the mixture decreases with height is numerically investigated. The change of modes “isothermal diffusion–gravitational concentration convection” caused by instability of mechanical equilibrium of the system was earlier investigated experimentally. A numerical study using “Species Transport Model” ANSYS Fluent modeled the mass transfer processes at different stages of diffusive and convective mixing. The approach demonstrated the presence of complex convective flow dynamics at small mixing times, which are difficult to realize in experiments. Reliability in reproducing quantitative values of concentrations during combined mixing for large relaxation times, which had been previously studied experimentally, was also noted. The presented results make it possible to analyze the mixing modes in multicomponent systems, which makes it possible to determine more correctly the regions of diffusion and convective perturbations.